Preoperative Cylex assay predicts rejection risk in patients with kidney transplant. (21st April 2014) - Myslik, Frank; House, Andrew A.; Yanko, Daniel; Warren, Jeff; Caumartin, Yves; Rehman, Faisal; Jevnikar, Anthony M.; Stitt, Larry; Luke, Patrick P.
Abstract Introduction and Objectives The ImmuKnow assay measures cell‐mediated immunity by quantifying ATP release from CD4+ T‐cells in peripheral blood. Herein, we hypothesized that this assay could predict complications associated with over‐/under‐immunosuppression in patients with kidney transplant (KT). Methods Sixty‐seven patients undergoing KT were recruited prospectively and had ATP levels measured preoperatively, and at specified intervals over two months. Clinicians were blinded to ATP levels. Clinical events including rejection and infection/cancer were documented with a median follow‐up of 21 months. Parameters including absolute ATP levels and changes in ATP patterns (slopes, delta) were analyzed. Association between ATP parameters and clinical outcomes was compared using the likelihood‐ratio test and Kaplan–Meier curves. Results Absolute ATP values postoperatively had poor predictive value with regard to rejection or infection/malignancy. As well, changes in ATP values were poorly associated with complications. Importantly, patients with pre‐transplant ATP values <300 ng/mL had significantly less rejection episodes vs. those with ATP values >300 ng/mL (p < 0.0001). Conclusions For the first time, we have evidence that a preoperative ImmuKnow level can stratify patients with KT into low/high risk groups for rejection. Future studies used to assess the utility of this assay to design individualized immunosuppressive regimens are required.